PEMERIKSAAN RADIOGRAFI COLON IN LOOP PADA BAYI MENGGUNAKAN KONTRAS POSITIF DENGAN KLINIS HIRSCHPRUNG DISEASE - Saleh Mursyid; Muh Amirul Mukminin; Hesti Andriyani Putri (JRI (Jurnal Radiografer Indonesia), 2023)
ABSTRACT Background: The development of radiology is growing rapidly because radiodiagnostics is a very important diagnostic tool and cannot be separated in a diagnosis. There are two radiodiagnostic examinations in radiology installations, namely without contrast media and radiological examinations with contrast media. One of the radiological examinations with contrast media is a colon in a circle. Methods: This research is a qualitative descriptive study conducted in April 2022. The sample in this study were patients who underwent Colon In Loop Examination in Infants Using Positive Contrast with Clinical Hirschsprung's Disease at the Radiology Installation of RSUD A.M Parikesit Tenggarong. Results: Insertion of contrast in colon in loop examination In infants using positive contrast with clinical Hirschsprung's disease can already establish a doctor's diagnosis. And from the results of the expertise with the doctor from the results of the picture the catheter was placed at the end of the baby's anus, the contrast was injected and it looked smooth closing the sigmoid rectum and descending colon, it looked like the distal rectum was narrowed and it looked like proximal rectal dilatation, an impression of hisprung disease. Conclusion: Colon in loop examination technique in infants to see clinically Hirschsprung's disease would be better to use positive contrast because it can be excreted through micturition and sweat and more thoroughly see narrowing, easier, better to see other abnormalities